Management of NSAID-related pyloric obstruction in a child using endoscopic balloon dilatation: A case report - Mustafa Onur Öztan; Gizem Güngör-Takeş; Yeliz Çağan-Appak; Coşkun Yıldız; Miray Karakoyun; Maşallah Baran (The Turkish Journal of Pediatrics)
A gastric outlet obstruction (GOO) is a major complication of peptic ulcers (PUs) and corrosive ingestion in children; however, the optimal management of a patient with a GOO after a PU remains controversial. Although surgical correction is the most common treatment option, endoscopic balloon dilatation and simultaneous dilatation with a steroid injection are used more frequently as first-line treatments for PU-related GOOs. These patients require operative interventions when the obstruction cannot be managed using endoscopic approaches or in cases of relapsing after the procedure. Here, we present a case to create awareness that endoscopic balloon dilatation is a simple, effective, and safe therapy for a PU-related GOO.